2017
DOI: 10.1111/jphp.12704
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of artemisinin against isoflurane-induced cognitive impairments and neuronal cell death involve JNK/ERK1/2 signalling and improved hippocampal histone acetylation in neonatal rats

Abstract: Artemisinin effectively inhibited neuronal apoptosis and improved cognition and memory via regulating histone acetylation and JNK/ERK1/2 signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In experimental animal models, isoflurane brings about mitochondrial dysfunction, neuroinflammation, and apoptosis, leading to cognitive impairments and neuronal cell death (Li et al, 2014; Hu X. et al, 2017; Liang et al, 2017; Su et al, 2017; Wu et al, 2017; Xu et al, 2017). Furthermore, it has been observed to modulate glutamate receptors.…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental animal models, isoflurane brings about mitochondrial dysfunction, neuroinflammation, and apoptosis, leading to cognitive impairments and neuronal cell death (Li et al, 2014; Hu X. et al, 2017; Liang et al, 2017; Su et al, 2017; Wu et al, 2017; Xu et al, 2017). Furthermore, it has been observed to modulate glutamate receptors.…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…Furthermore, it has been observed to modulate glutamate receptors. One study has reported that NMDAR-mediated excitatory synaptic transmission is more sensitive to isoflurane than non-NMDAR-mediated excitatory synaptic transmission (Xu et al, 2017). In addition, at minimum alveolar concentrations, isoflurane causes GABA A receptor antagonism and increases NMDARs inhibition (Nishikawa and MacIver, 2000).…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%
“…In another study, clinically relevant concentrations of artemisinin were demonstrated to protect and rescue neuronal PC12 cells from the cell death induced by amyloid beta-peptide 25–35 (Aβ 25-35 ), during which artemisinin was verified to act as a neuronal protectant from Aβ 25-35 insult via activation of the ERK1/2 pathway ( Zeng Z. et al, 2017 ). Furthermore, the neuroprotective effect of artemisinin was assessed by the exposure of neonatal rats to the neurotoxin isoflurane, and artemisinin was found to exhibit an inhibitory effect on isoflurane-induced neuronal cell death and ameliorate cognitive impairment and memory loss by modulating histone acetylation and signal transduction through the c-Jun N-terminal kinase (JNK) and ERK1/2 pathways ( Xu G. et al, 2017 ).…”
Section: Artemisinin Targets Receptors Impacting On Signaling Cascadementioning
confidence: 99%
“…These identified genes were also related to a list of Gene Ontology (GO) terms and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. For example, the pathways involve "complement and coagulation cascades," which have been reported to play important roles in the progression of DKD (Wang et al, 2016c), and the "p53 signaling pathway" and "TGF-β signaling pathway," which are closely associated with DKD (Zhang et al, 2011;Wang et al, 2016a;Mukhi et al, 2017;Xu et al, 2017a;Shelbaya et al, 2018;Sheng et al, 2018;Xiang et al, 2019). These results indicate promising targets in the treatment of DKD with artemisinins.…”
Section: Type 2 Diabetes Mellitus-related Complications Diabetic Kidnmentioning
confidence: 88%